2021
DOI: 10.3390/ma14164468
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Thrust Force, Delamination and Surface Roughness in Drilling Hybrid Structural Composites

Abstract: Filled hybrid composites are widely used in various structural applications where machining is critical. Hence, it is essential to understand the performance of the fibre composites’ machining behaviour. As such, a new hybrid structural composite was fabricated with redmud as filler and sisal fibre as reinforcement in polyester matrix. The composite was then tested for its drilling performance. A comprehensive drilling experiment was conducted using Taguchi L27 orthogonal array. The effect of the drill tool po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Various common methods are employed to mitigate this problem. These include the manufacture of drills with varied shapes and quality levels, adjusting cutting parameters for optimization, and implementing peck drilling techniques [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various common methods are employed to mitigate this problem. These include the manufacture of drills with varied shapes and quality levels, adjusting cutting parameters for optimization, and implementing peck drilling techniques [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…This laminated Al–PE composite also undergoes a drilling process for mounting applications. Numerous studies in the literature discuss the mechanical and machining characterization of such materials [ 11 , 12 , 13 ]. For instance, Gao et al [ 14 ] reported that, when the bonding strength of the steel/Al/steel composite interface is low, delamination first occurs on the exterior of the bending, as seen in their study on the effect of bond strength on the formability of steel/aluminum composite panels.…”
Section: Introductionmentioning
confidence: 99%
“…These composites attract more attention in modern applications, especially in many engineering structures and constructions because of their light weight and increased strength compared to conventional materials. 5 Aluminum Alloys are soft and high strength materials. 7075 aluminum alloy used as a matrix material in this study is one of the most widely used non-ferrous materials in engineering applications due to its attractive properties such as high strength to weight ratio, good ductility, excellent corrosion, availability, and low cost.…”
Section: Introductionmentioning
confidence: 99%